Servicecape Analysis To Customer Satisfaction In Delivery Service Company With Customer Trust As Intervening Variable - Mulyono, Hardi; Fikri, Muhammad Hilman; Syamsuri, Abd Rasyid (Jurnal Manajemen Industri dan Logistik, 2023)
The number of people who send goods to each other  makes delivery services very important. The development of internet technology  has a great  contribution to the community  need for goods delivery services. For  buying and selling goods business , it is not only limited to face-to-face but  also be done through online media. This research was  conducted using sampling technique namely convenience sampling with consideration of convenience, such as respondents who are easier to find by researchers (Sugiarto, 2011). Respondents in this study were   Costumer s who use delivery service companies with the following criteria: Have used delivery services in the last six months. The number of respondents used was  as many as 120 respondents with 22 types of attributes in the questionnaire. The results of the study showed that there was a positive and significant relationship between the servqual variable and  Costumer  trust; there was  no positive and significant effect between servicecape variables on  Costumer  trust; service quality on  Costumer  loyalty did  not have a significant and positive effect; there was  no effect of servicecape on  Costumer  loyalty; there was  a positive and significant effect of the  Costumer  trust variable on  Costumer  loyalty.